2018
DOI: 10.1634/theoncologist.2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

EML4-ALK Rearrangement and Its Therapeutic Implications in Inflammatory Myofibroblastic Tumors

Abstract: This case exemplifies the heterogeneous behavior of inflammatory myofibroblastic tumors (IMTs) and the current role of targeted therapy in the therapeutic armamentarium of neoplastic processes.As evidenced by the different mutations found in IMTs, it is of great importance to perform next-generation sequencing in uncommon neoplasms.These studies can find different potential targets and therapeutic options for patients devoid of standard effective therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this study, both primary and metastatic lesions of the two IMTs were positive for ALK and harbored EML4 (exon 6)-ALK (exon 20) fusion. To date, eighteen EML4-ALK fusion IMTs have been reported (including the present two IMTs) (8,(13)(14)(15)(16)(17)(18)(19)(20) (Supplementary Table 3), eleven of which are located in the lung (11/18, 61.1%). The other cases included two IMTs in the abdominopelvic cavity, two IMTs in the limbs, one IMT in the head, one IMT in the trachea, and one IMT in the hypopharynx.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, both primary and metastatic lesions of the two IMTs were positive for ALK and harbored EML4 (exon 6)-ALK (exon 20) fusion. To date, eighteen EML4-ALK fusion IMTs have been reported (including the present two IMTs) (8,(13)(14)(15)(16)(17)(18)(19)(20) (Supplementary Table 3), eleven of which are located in the lung (11/18, 61.1%). The other cases included two IMTs in the abdominopelvic cavity, two IMTs in the limbs, one IMT in the head, one IMT in the trachea, and one IMT in the hypopharynx.…”
Section: Discussionmentioning
confidence: 85%
“…Thirty-seven patients underwent ALK immunostaining, and 19 patients demonstrated positive results. Gene detection was only performed in 10 patients, and 8 patients had ALK rearrangements, including 3 patients with EML4-ALK fusions (8,(14)(15)(16)(17)(18)(19)(20)(21). Although several studies have demonstrated EML4-ALK fusions in up to 20% of ALK-rearranged IMTs (8), the association between different EML4-ALK fusion variants and IMT disease progression has been insufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its biological characteristics, the discovery that IMT may harbor chromosomal rearrangements at the 2p23 Locus, where the gene site for anaplastic lymphoma kinase (ALK) is, also firmed the borderline neoplasm property of IMT[ 6 - 8 ]. According to several case reports, approximately 30 kinds of genetic rearrangement have been found in IMT, most of which are ALK fusion genes[ 9 - 12 ]. ALK can be detected in about 50% of IMTs[ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most IMTs are associated with ALK rearrangements, but other tyrosine kinase genes, such as ROS1 and RET, rearrangements can be the driver event (3,26). Interestingly, one of the ALK gene fusion partners described in IMT is EML4, and EML4::ALK rearrangements are frequent in non-small cell lung adenocarcinoma (27,28).…”
mentioning
confidence: 99%